United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper on United States 2012 Article IV Consultation discusses rebound of manufacturing production. The U.S. share in global manufacturing production declined through most of the past three decades, but it has stabilized since the Great Recession. It currently represents about 20 percent of global manufacturing value added. Interestingly, after a sharp increase during most of the previous decade, China's share in global manufacturing has also stabilized since the Great Recession, at a level similar to that of the United States. The notion of a manufacturing renaissance has been fuelled partly by the rebound in production since the end of the Great Recession.